Concurrent structural topology and injection gate location optimization for injection molding multi-material parts - Fu, Junyu; Zhang, Xiaogang; Quan, Long; Ma, Yongsheng (Advances in engineering software (1992), 2022)
•A novel concurrent optimization algorithm is proposed to simultaneously optimize the structural geometry and injection gate locations for multi-material plastic parts.•A novel level set-based voronoi diagram generation algorithm is developed to simulate the weld-line formation.•Several numerical examples are used to show the effectiveness of the proposed method. This paper develops a novel concurrent optimization algorithm to simultaneously optimize the structural geometry and injection gate locations, dedicated to injection molding multi-material part design. Specifically, level set method is employed for structural shape and topology optimization. Different from the existing methods which count on the combination of different level set functions to represent the multi-material distribution, a novel level set-based Voronoi diagram generation algorithm is developed to simulate the weld-line formation, thus determining the material-material interfaces, since the multi-material distribution from injection molding is strongly dependent on the injection gate locations and the fluid flow condition. Then, the sensitivity of multi-material distribution against the injection gate location variables is calculated with a finite difference-based approach. Two sets of numerical examples are investigated to demonstrate the effectiveness of the proposed method. It is observed that the structural topology optimization with simultaneous injection gate location optimization for compliance minimization leads to improved multi-material design solutions than the cases with fixed injection gate locations.